2016
DOI: 10.1016/j.molmet.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon receptor gene deletion in insulin knockout mice modestly reduces blood glucose and ketones but does not promote survival

Abstract: ObjectiveIt has been thought that the depletion of insulin is responsible for the catabolic consequences of diabetes; however, evidence suggests that glucagon also plays a role in diabetes pathogenesis. Glucagon suppression by glucagon receptor (Gcgr) gene deletion, glucagon immunoneutralization, or Gcgr antagonist can reverse or prevent type 1 diabetes in rodents suggesting that dysregulated glucagon is also required for development of diabetic symptoms. However, the models used in these studies were rendered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Studies in glucagon receptor knockout mice rendered insulin deficient by streptozotocin have firmly demonstrated the metabolic benefits of absence of glucagon action without insulin administration . In addition, we have shown in mice with near absence of insulin receptor signaling that REGN1193 treatment is able to lower glucose to near normal ranges .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Studies in glucagon receptor knockout mice rendered insulin deficient by streptozotocin have firmly demonstrated the metabolic benefits of absence of glucagon action without insulin administration . In addition, we have shown in mice with near absence of insulin receptor signaling that REGN1193 treatment is able to lower glucose to near normal ranges .…”
Section: Discussionmentioning
confidence: 66%
“…Studies in glucagon receptor knockout mice rendered insulin deficient by streptozotocin have firmly demonstrated the metabolic benefits of absence of glucagon action without insulin administration. [18][19][20] In addition, we have shown in mice with near absence of insulin receptor signaling that REGN1193 treatment is able to lower glucose to near normal ranges. 21 Thus, patients with insulin receptor loss of function mutations, manifested as severe insulin resistance and diabetes, ie, Rabson-Mendenhall syndrome and other related diseases, may benefit from anti-glucagon receptor therapy.…”
Section: Discussionmentioning
confidence: 83%
“…In particular, genetic deletion of insulin (49) or the use of diphtheria toxin to induce near complete ablation of β-cells (50) in Gcgr −/− mice nonetheless induced full-blown diabetes. Thus, it has been suggested that a retained low level of insulin, as occurs in the STZ type 1 diabetes model, may be permissive for the blood glucose–lowering effect observed with GcgR antagonism.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels of glucagon are aberrantly increased in individuals with T2DM 171174 . In addition, animal models of reduced or ablated glucagon action show improvements in T2DM 96,175,176 (FIG. 4a,b).…”
Section: Targeting Hepatic Glucose Productionmentioning
confidence: 99%